2015
DOI: 10.1016/j.egypro.2015.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Wind Engineering Analysis of Parabolic Trough Collectors to Optimise Wind Loads and Heat Loss

Abstract: Concentrating Solar Power (CSP) plants tend to be located in open areas. This leads to the power plant usually being subjected to high wind speeds without much shelter or protection. In parabolic trough plants the solar field, the collectors and receiver tubes, are affected by the wind on both the structural, as well as the performance level. The collectors must resist the aerodynamic forces caused by the wind, and the airflow around the receiver tube has a cooling effect on it. The effects of the wind on Para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Huang et al (2015) presented a simulation study of the fully developed turbulent flow and heat transfer in the receiver tube with and without protrusions, helical fins, and dimples and concluded that the receiver tubes with dimples have higher performance compared to all other configurations. Paetzold et al (2015) investigated the effect of wind on structure and performance of the PTC field. Fuqiang et al (2016) proposed a symmetric outward, convex, and corrugated receiver tube design.…”
Section: Parabolic Trough Collectormentioning
confidence: 99%
“…Huang et al (2015) presented a simulation study of the fully developed turbulent flow and heat transfer in the receiver tube with and without protrusions, helical fins, and dimples and concluded that the receiver tubes with dimples have higher performance compared to all other configurations. Paetzold et al (2015) investigated the effect of wind on structure and performance of the PTC field. Fuqiang et al (2016) proposed a symmetric outward, convex, and corrugated receiver tube design.…”
Section: Parabolic Trough Collectormentioning
confidence: 99%
“…Mier-Torrecilla et al [29] conducted a CFD analysis to obtain the wind loads in a single model PTC under different yaw and pitch angles, and the results were compared with wind-tunnel experiments. Like Mier-Torrecilla, Paetzold et al [30] made a similar CFD analysis but used three different focal length of the parabola. Naeeni and Yaghoubi [31] performed a two-dimensional CFD analysis of a PTC under different wind velocities and pitch angles to observe the flow behavior around the collector.…”
Section: Supporting Structurementioning
confidence: 99%
“…The initial conditions were uniform fully developed velocity profile at PTC inlet. K‐ω SST turbulence model is chosen 41 . The first‐order upwind discretization scheme was used for the momentum equation, continuity equation, energy equation, turbulence kinetic energy ( k ), and turbulence dissipation rate ( ε ).…”
Section: Computational Fluid Dynamics Analysis Of the Ptcmentioning
confidence: 99%